"THE DEAD MAN COME TO LIFE AGAIN": EDWARD ALBERT AND THE STRATEGIES OF BLACK ENDURANCE. Issue 2 (5th May 2017) - Prizel, Natalie
Abstract : This essay tells a story of endurance: the endurance of a person and the endurance of an object in an archive, both of which have survived despite their apparent fungibility and ephemerality. It focuses on a Jamaican veteran of the navy and merchant marine – one Edward Albert – who lost his legs while at sea and therefore took to working at various intervals as a crossing sweeper, beggar, shop-owner, and author in London and Glasgow. Albert should have been lost. His shipmates burnt his legs to the point of bursting, and his doctors presumed him to be dead following their amputation. I located Edward Albert initially in the pages of Henry Mayhew's massive, unwieldy, almost unnavigable archive, the four volumes of London Labour and the London Poor . Mayhew interviews Albert in his home and then refers to a small chapbook Albert sells to accompany his begging. A simple WorldCat search led me to a copy of the book, housed at the University of Washington in Seattle. It had endured.